The Role and Importance of the Sejm State Control Committee - Worach, Sławomir (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The article concentrates on the issue of establishing and activities of the Sejm (Polish parliament) State Control Committee which has special character and as for the principle is to fulfill the role of the main centre to effectuate one of the most fundamental functions of the Sejm, namely the control function. There is the detailed description of the origin of this committee with regard to the political context of this decision and arguments for and against establishing this committee during the parliamentary debate concerning foundation of this body. There is formal-legal analysis of the competencies and the range of activities of this committee and also established in the course of practice direction of its functioning. The analysis of almost ten-year history of its practical activity has provided the image of practical possibilities to fulfill its control function as well as its weaknesses. The conducted research with legal and comparative analysis of similar parliamentary committees in other countries led to the conclusion that the State Control Committee hasn’t managed to work out the optimal range of its operation so its identity and ultimate competencies are still being searched. There is no doubt, however, that it plays auxiliary role in the execution of the Sejm’s control function and in the age of specialization of legislative bodies through the multiplication of specialist committees the committee certainly has its permanent standing in Polish Sejm.